EVALUATION OF THE NURSING APPROACH IN THE CARE OF PATIENTS WITH DIABETES (CIPEEX, 2025)
Diabetes mellitus is a chronic disease that requires continuous care and a multidisciplinary approach for blood glucose control and the prevention of complications. In the context of nursing, various strategies are employed to improve care for diabetic patients, such as health education, regular monitoring, promotion of treatment adherence, and psychological support. Nursing plays a fundamental role in preventing potential complications for people with diabetes, such as cardiovascular diseases and nephropathy, in addition to promoting humane and empathetic care. This study aimed to explore the role of nursing in the care of patients with diabetes. As a research instrument, a questionnaire developed by the authors themselves was used, containing 12 multiple-choice questions, applied to 18 diabetic patients of both genders, aged between 28 and 42 years, residing in the city of Uruana - GO. The results showed that 75% of the participants face difficulties in managing the disease, especially in glycemic control and complication management. Additionally, palliative care proved to be important in improving quality of life, alleviating physical symptoms, and providing emotional support. Data analysis revealed that a patient-centered nursing approach, integrated with a multidisciplinary team, is essential for improving well-being and satisfaction with treatment. The multidisciplinary health team plays a crucial role in the comprehensive care of diabetic patients, contributing to the improvement of quality of life through clear and objective communication about the patient's situation and viable treatments, considering their financial, emotional, and social condition. It is also noteworthy that the study participants praised the care received from the multidisciplinary team, evaluating it as positive and essential for managing their condition. They reported feeling very well supported by the nursing team, highlighting the individualized attention and continuous support provided throughout the treatment process. This support was perceived as an important factor for treatment adherence and the development of self-care, as, according to the patients, the team demonstrates empathy, clarity in guidance, and sensitivity in understanding their needs and limitations, creating an environment of trust and security in facing diabetes. It is concluded that, for effective diabetes management, it is essential to promote health policies that include palliative care and professional training, ensuring more humanized and efficient care for diabetic patients.
Keywords: Nursing; Approach; Care; Diabetes